The Clinical and Economic Impact of Measles-Mumps-Rubella Vaccinations to Prevent Measles Importations From US Pediatric Travelers Returning From Abroad. Issue 6 (25th March 2022) - Bangs, Audrey C; Gastañaduy, Paul; Neilan, Anne M; Fiebelkorn, Amy Parker; Walker, Allison Taylor; Rao, Sowmya R; Ryan, Edward T; LaRocque, Regina C; Walensky, Rochelle P; Hyle, Emily P
Abstract: Background: Pediatric international travelers account for nearly half of measles importations in the United States. Over one third of pediatric international travelers depart the United States without the recommended measles-mumps-rubella (MMR) vaccinations: 2 doses for travelers ≥12 months and 1 dose for travelers 6 to <12 months. Methods: We developed a model to compare 2 strategies among a simulated cohort of international travelers (6 months to <6 years): (1) No pretravel health encounter (PHE): travelers depart with baseline MMR vaccination status; (2) PHE: MMR-eligible travelers are offered vaccination. All pediatric travelers experience a destination-specific risk of measles exposure (mean, 30 exposures/million travelers). If exposed to measles, travelers' age and MMR vaccination status determine the risk of infection (range, 3%-90%). We included costs of medical care, contact tracing, and lost wages from the societal perspective. We varied inputs in sensitivity analyses. Model outcomes included projected measles cases, costs, and incremental cost-effectiveness ratios ($/quality-adjusted life year [QALY], cost-effectiveness threshold ≤$100 000/QALY). Results: Compared with no PHE, PHE would avert 57 measles cases at $9.2 million/QALY among infant travelers and 7 measles cases at $15.0 million/QALY among preschool-aged travelers. Clinical benefits of PHE would be greatest for infants but cost-effective only for travelers to destinations with higher risk for measles exposure (ie, ≥160 exposures/million travelers) or if more US-acquired cases resulted from an infected traveler, such as in communities with limited MMR coverage. Conclusions: Pretravel MMR vaccination provides the greatest clinical benefit for infant travelers and can be cost-effective before travel to destinations with high risk for measles exposure or from communities with low MMR vaccination coverage. Abstract : Pretravel health visits that provide the recommended measles-mumps-rubella vaccination to eligible pediatric international travelers were cost-effective for infants traveling to destinations with high exposure risk when more than 8 US-acquired cases resulted from each measles importation.